2019
DOI: 10.3926/jotse.662
|View full text |Cite
|
Sign up to set email alerts
|

A sequential explanatory investigation of TPACK: Indonesian science teachers’ survey and perspective

Abstract: This sequential explanatory design aims at exploring science teachers’ survey and perceptions of technology integration regarding to technological pedagogical content knowledge (TPACK) which focused on quantitative findings supported by qualitative findings. It involved 356 respondents for the survey and eight participants for the interview. Descriptive statistics, T-test and Anova were used in quantitative data analysis while for qualitative data analysis, thematic process was conducted. Findings show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 34 publications
4
14
0
10
Order By: Relevance
“…Thus, the study also uncovered that few teachers (not only in rural areas) found difficulties in managing digital learning as they found technology did not make any changes to students' learning and they admitted they did not give feedback and conduct assessment to students. In this case, the teachers TPACK (Technological Pedagogical Content Knowledge) need further investigation for the success of digital learning (Redmond & Lock, 2019;Muhaimin, et al, 2019) in this situation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the study also uncovered that few teachers (not only in rural areas) found difficulties in managing digital learning as they found technology did not make any changes to students' learning and they admitted they did not give feedback and conduct assessment to students. In this case, the teachers TPACK (Technological Pedagogical Content Knowledge) need further investigation for the success of digital learning (Redmond & Lock, 2019;Muhaimin, et al, 2019) in this situation.…”
Section: Discussionmentioning
confidence: 99%
“…Pencarian kelayakan artikel dan artikel yang terpilih untuk tinjauan dalam penelitian ini diringkas dalam bagan dibawah ini, dilakukan secara sistematis dengan mengikuti tahapan yang benar dengan menggunakan format PRISMA (Muhaimin et al, 2019).…”
Section: Metode Penelitianunclassified
“…Perkembangan teknologi kini semakin pesat, yang dikenal dengan revolusi industri 4.0. Revolusi industri 4.0 telah masuk di segala bidang kehidupan termasuk bidang pendidikan (Muhaimin et al, 2019;Prasojo et al, 2017). Perkembangan ini menuntut dunia pendidikan untuk mengintegrasikan teknologi agar dapat mempermudah aktivitas pembelajaran.…”
Section: Pendahuluanunclassified